The Promise of Targeting Hypoxia to Improve Cancer Immunotherapy: Mirage or Reality? - Janji, Bassam; Chouaib, Salem (Frontiers in Immunology, 2022)
Almost all solid tumors display hypoxic areas in the tumor microenvironment associated with therapeutic failure. It is now well established that the abnormal growth of malignant solid tumors exacerbates their susceptibility to hypoxia. Therefore, targeting hypoxia remains an attractive strategy to sensitize tumors to various therapies. Tumor cell adaptions to hypoxia are primarily mediated by hypoxia-inducible factor-1 alpha (HIF-1α). Sensing hypoxia by HIF-1a impairs the apoptotic potential of tumor cells, thus increasing their proliferative capacity and contributing to the development of a chaotic vasculature in the tumor microenvironment. Therefore, in addition to the negative impact of hypoxia on tumor response to chemo- and radio-therapies, hypoxia has also been described as a major hijacker of the tumor response by impairing the tumor cell susceptibility to immune cell killing. Here, we first provide a comprehensive overview of the mechanisms involved in the establishment of hypoxic stress in the tumor microenvironment. We then summarize recent knowledge on how hypoxia contributes to tumor escape from immune surveillance. We also provide preclinical proof of concept showing the value of targeting hypoxia as a strategy to improve the therapeutic benefit of cancer immunotherapy.